The roles of PDZ-containing proteins in PLC--mediated signaling. - Suh, P.G.; Hwang, J.I.; Ho Ryu, S.; Donowitz, M.; Ho Kim, J. (Biochemical and Biophysical Research Communications, 2001)
Mammalian phospholipase C-beta isozymes are activated by a heterotrimeric GTP-binding protein linked to various cell surface receptors. Recent reports suggest that PDZ domain proteins play a significant role of PDZ-containing proteins in the regulation of mammalian PLC-beta isozymes. PDZ-containing proteins mediate the clustering of receptors and signaling molecules and thereby regulate agonist-induced signal transduction in polarized cells such as neuronal and epithelial cells. NORPA, a Drosophila PLC-beta, is known to be a component of a signaling complex that includes TRP and rhodopsin through interaction with INAD, a PDZ-containing protein. Mammalian PLC-beta1 and -beta2 isoforms interact with a PDZ-containing protein NHERF which is coupled to Trp4, a Ca(2+) channel. In addition, PLC-beta3 specifically interacts with E3KARP, another protein closely related to NHERF, through its C-terminal PDZ-binding motif. E3KARP up-regulates the PLC-beta3 activation coupled to muscarinic receptor. In this review, the role of signaling complexes mediated by PDZ-containing proteins in the regulation of PLC-beta isoforms will be discussed.